2021
DOI: 10.3390/genes12111776
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ Metabolism and Diseases with Motor Dysfunction

Abstract: Neurodegenerative diseases result in the progressive deterioration of the nervous system, with motor and cognitive impairments being the two most observable problems. Motor dysfunction could be caused by motor neuron diseases (MNDs) characterized by the loss of motor neurons, such as amyotrophic lateral sclerosis and Charcot–Marie–Tooth disease, or other neurodegenerative diseases with the destruction of brain areas that affect movement, such as Parkinson’s disease and Huntington’s disease. Nicotinamide adenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 176 publications
(211 reference statements)
1
11
0
Order By: Relevance
“…Alternatively, the different metabolic phenotypes observed in brain and SPC under the same metabolic constraints can be the result of disparities in the expression or regulation of the components of the NAD + :NADH pathways and/or the shuttling of NAD + :NADH between mitochondria and the cytosol. In agreement, previous evidence has demonstrated that MNs are particularly sensitive to changes in NAD + :NADH ratio and that reductions in NAD + could be a common phenomenon in motor neuron disorders (Lundt and Ding, 2021;Obrador et al, 2021).…”
Section: (See Fig 4 Right Panels)supporting
confidence: 92%
“…Alternatively, the different metabolic phenotypes observed in brain and SPC under the same metabolic constraints can be the result of disparities in the expression or regulation of the components of the NAD + :NADH pathways and/or the shuttling of NAD + :NADH between mitochondria and the cytosol. In agreement, previous evidence has demonstrated that MNs are particularly sensitive to changes in NAD + :NADH ratio and that reductions in NAD + could be a common phenomenon in motor neuron disorders (Lundt and Ding, 2021;Obrador et al, 2021).…”
Section: (See Fig 4 Right Panels)supporting
confidence: 92%
“…also reported that NAD + supplementation could be utilized in a broad spectrum of NAD + deficiency‐related pathologies, such as cancer, infection, acute injury, metabolism‐related disorders, and neurodegenerative diseases. [ 50–52 ]…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al also reported that NAD + supplementation could be utilized in a broad spectrum of NAD + deficiency-related pathologies, such as cancer, infection, acute injury, metabolism-related disorders, and neurodegenerative diseases. [50][51][52] Mitochondria, as energy plants, participate in signal transmission, cell differentiation, oxidative stress reactions, and calcium homeostasis. [53] Triphenylphosphonium cation (TPP + ) is the most adopted moiety that can easily and efficiently permeate the mitochondrial inner membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Playing a key role in energy transduction and cell signal transduction, NAD+ can be transformed into NADP, NAADP and cADPR ( 4 , 5 ). Moreover, NAD+ degradation products, such as nicotinamide and N-methyl nicotinamide, have also been considered as key regulators of energy metabolism, epigenetics and disease status ( 6 8 ). NAD+ pathway metabolites can also serve as substrates for a group of diverse enzymes ( 9 , 10 ), including SARM1, ARTs, PARPs, CD38, sirtuins, and RNA polymerases, which were involved in several aspects of cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%